(untitled) (American Journal of Islam and Society, 2006)
This most interesting and ground-breaking study presents a Foucauldian and Nietzschean genealogical tracing of the concept of the secular, working back from the present to the contingencies that have coalesced to produce current certainties. It asks what an “anthropology of secularism” might look like and examines the connection between the “secular” as an epistemic category and “secularism” as a political doctrine. Asad attempts to avoid the trap of making pronouncements about secularism’s virtues and vices, irrespective of its origin, and to proffer instead an anthropological formulation of its doctrine and practice. According to the author, secularism is more than a mere separation of religious from secular institutions of government, for it presupposes new concepts of religion, ethics, and politics; as well as the new imperatives associated with them, and is closely linked to the emergence of the modern nation-state (pp. 1-2). In contrast to pre-modern mediations of nontranscended local identities, secularism is a redefining, transcending, and differentiating political medium (representation of citizenship) of the self, articulated through class, gender, and religion (p. 5). Concomitantly, he questions the secular’s self-evident character even when admitting the reality of its “presence” (p. 16). His main premise is that “the secular” is conceptually prior to the political doctrine of secularism, the secular being that formation caused by a variety of concepts, practices, and sensibilities that have come together over time (p. 16). He concludes that the “secular” cannot be viewed as the “rational” successor to “religion,” but rather as a multilayered historical category related to the major premises of modernity, democracy, and human rights. Within the above introductory framework, the book’s seven chapters are divided into three parts. The first part, comprising three chapters, explores the epistemic category of the secular. The following three chapters of part 2 ...